synthesis and characterization of nano alumina by gel combustion menthod - MISGANAW BERHANU ADDIS, MISGANAW BERHANU ADDIS (2009)
This paper reports the synthesis of nano sized alumina powders by the combustion method using urea and citric acid as fuels. The effect of the three factors, which are type of fuel- urea/citric acid, fuel to oxidizer ratio and PH of the starting solution, on the thermal decomposition characteristics of alumina precursor and the properties of nanocrystalline alumina synthesized using this gel combustion process. The technique involves the combustion of a urea/citrate-nitrate gel occurring between Al(NO3)3 and urea/citric acid to yield an ash powder that upon calcination at 1373 K produced nano alumina. The ignition was restricted to a particular range of urea/citrate to nitrate ratio in the gel. Once the powder is synthesized, the product was characterized by SEM. The resulting powder exhibited fine crystallite size. It was established from various characterization techniques that the alumina powder prepared with a stoichiometric urea to oxidizer ratio and PH of 10 and citric acid to oxidizer ratio of 1.5 and pH of 10 has got the optimum powder characteristics compared to the rest of the batches. This shows the importance of maintaining a stoichiornetric or near stoichiometric urea to oxidizer ratio and maintain above stoichiometric ratio of citric acid to oxidizer. Generally, the process has a higher degree of reproducibility and a good potential for large-scale production of alumina.